Sektor Potensial Sebagai Backbone pada Kabupaten Berbasis Sektor Pertambangan di Kalimantan Selatan - Muzdalifah Muzdalifah; Syahrituah Siregar; Ayu Fitriani; Norlatifah Norlatifah (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
This study identifies potential economic sectors as key drivers in mining-based regencies of South Kalimantan by analyzing inter-sectoral linkages (forward-backward linkages), value-added, and economic impacts. Using Input-Output analysis and Klassen typology on 2016 data covering 17 sectors, the study identifies leading sectors capable of driving economic growth amid declining contributions from the extractive sector. The results highlight Processing Industry, Waste Management, Information/Communication, Accommodation, and Real Estate as key sectors with varying dominance across regencies: Tanah Bumbu (Processing, Waste, Information), Kotabaru (Processing, Waste, Accommodation, Real Estate), and Balangan & Tabalong (Processing, Waste, Information, Accommodation, Real Estate). The novelty of this research lies in combining Input-Output and Klassen analyses to integrate linkages with income-output multiplier effects, providing accurate policy recommendations for inclusive post-mining economic development.